Heteroglossia and dialogism in Shuntarô Tanikawa's poetry - Taranco, David (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Poetry, in its analysis, has been deprived of elements such as dialogism, heteroglossia and polyphony, all of them introduced by the Russian theorist Mikhail Bakhtin (1895-1975) in the first half of the 20th century and applied ever since to the novel. Through this essay I intend to make use of those same resources to analyse two poems from Yoru no Mickey Mouse, by the Japanese poet Shuntarô Tanikawa (1931-), in order to return poetry the dialogic ability that it has been steadily dispossessed of, being as it was constrained to the particular and closed universe of the lyrical speaker.
Keywords: Poetry; Bakhtin; heteroglossia; dialogism; Tanikawa; Japan.